GDP and TFP in poviats of the Łódzkie voivodeship. Estimation and analysis of differentiation - Dańska-Borsiak, Barbara (PKB i TFP w powiatach województwa łódzkiego. Oszacowanie i ocena zróżnicowania, 2022)
The main objective of the research was to estimate the level of GDP and total factor productivity (TFP) in the counties (‘poviats’) of the Łódzkie voivodeship in the period 2002-2019. The gross product in poviats was determined by disaggregating the GDP of the Łódzkie voivodeship in proportion to the revenues of poviat budgets from personal income tax PIT and to the shares of poviats in the voivodeship wage fund. TFP was determined on the basis of a labour productivity model derived from the Cobb-Douglas production function with the assumption of constant returns to scale. A spatial panel data model estimated by the maximum likelihood method was applied. The poviat of Łódź was identified as the upper outlier in terms of the level of gross product. The dynamics of poviat values of GDP was similar to the national one, but poviats with a much faster rate of growth were identified. The highest level of TFP was observed in the poviat of Łódź. Very high productivity was also characteristic for the two other cities with poviat status, especially Skierniewice. In the Łódzkie voivodeship there was a progressive polarisation in terms of TFP with two leading poviats. No spillover processes were found. The capital city of the voivodeship, being itself the upper outlier, therefore did not play the role of a growth centre. It was also found that a clearly defined profile of economic activity in the poviat is conducive to faster TFP growth.
Econometrics = Ekonometria, 2022, Vol. 26, No. 1, s. 14-30
Keywords: total factor productivity; GDP; poviat; spatial panel data model; łączna produktywność czynników produkcji; PKB; powiat; przestrzenny model danych panelowych